Analisis Penyajian Laporan Laba Rugi, Pengakuan Pendapatan dan Beban UMKM Berdasarkan SAK EMKM (Studi Kasus Pada Kedai Hobi Kopi Ambulu Jember) - Susanti, Indria Yuli; Fariana, Rina; Setiawan, M. Erik (Program Studi Akuntansi Fakultas Ekonomi Universitas PGRI Argopuro Jember, 2024)
Micro, small and medium enterprises (MSME) are currently developing very rapidly in Indonesia. MSME are required to prepare financial reports on their businesses periodically. MSME Accounting and Financial Standard for Micro, Small and Medium Entities were prepared by the Indonesian Institute of Accountants to provide standards for MSME financial reports. The aim of this research is to find out whether the preparation of Hobi Kopi Shop profit and loss report is in accordance with MSME Accounting and Financial Standard and whether the presentation and recognition of income and expenses is in accordance with generally accepted accounting principles. The results of the research show that Hobi Kopi Shop has not prepared financial reports in accordance with MSME Accounting and Financial Standard. The presentation and recognition of income at Hobi Kopi Shop is in accordance with accounting standards, however expenses are still not in accordance with generally accepted accounting standards. Keywords: MSME Accounting and Financial Standard, presentation of profit and loss statements, income recognition, expense recognition